Multidimensional human capital, wages and endogenous employment status in Ghana - Niels-Hugo Blunch (Institute for the Study of Labor (IZA), 2008)
Previous studies of labor market outcomes such as employment and wages have mostly been limited to investigating the impact of formal schooling only and, as a consequence, have seldom considered skills or alternative routes to acquiring skills, such as adult literacy programs, or other types of education. This paper examines these issues for Ghana, by estimating the joint effects of formal schooling, literacy and numeracy skills, and adult literacy programs on employment and wage outcomes. Wage and employment status equations are estimated jointly, allowing employment status to be endogenous. Substantial returns to basic cognitive skills are established, while the education system -especially the lower levels of formal education - is found to be relatively successful in creating these skills. At the same time the results hint at there being substantial returns to skills other than basic literacy and numeracy. These skills appear to be produced mostly from technical and vocational education and training and at higher levels of formal education. Adult literacy participants are less likely to be economically inactive and more likely to be self-employed, hinting at the income-generating activities component of these programs having indirect effects on wages through its effect on labor market participation, especially for females, individuals with no formal education, and in urban areas.
urn:nbn:de:101:1-20090107127
Keywords: I31; J24; O15; 330; Wage equations; employment status; human capital; literacy and numeracy; cognitive and non-cognitive skills; formal education; adult literacy programs; Ghana; Bildungsinvestition; Erwachsenenbildung; Wirkungsanalyse; Beschäftigungseffekt; Bildungsertrag; Ghana